Pengaruh Hospitalisasi terhadap Tingkat Kecemasan pada Anak Pra Sekolah di Rumah Sakit Permata Medika Semarang - Wahyuningsih Wahyuningsih; Niken Sukesi (Jurnal Kesehatan Amanah, 2024)
Hospitalization is a state of crisis in children when they are sick and hospitalized. This condition occurs because children try to adapt to a foreign and new environment, namely the hospital, so that this condition becomes a stressor factor for children and their families. Anxiety as an emotional state that has characteristics of physiological arousal, unpleasant feelings of tension, and fear that something bad will happen. Anxiety responses in toddlers are indicated by crying, protesting, reacting with anger, strong emotions, restlessness and screaming Pain and anxiety are two things that are interrelated and influence each other. Pain can cause children to feel afraid and anxious.The purpose of this study was to determine the effect of hospitalization and anxiety levels in preschool children at Permata Medika Hospital.Method: This type of research is quantitative, with a cross-sectional approach, where the cause variable or independent variable and the effect variable or dependent variable are measured at the same time and for a moment.The results of the study showed that there was a significant effect between hospitalization and children's anxiety levels with a significance value (p) of 0.000. hospitalization on children's anxiety levels. Thus, the better the Hospitalization, the lower the Child's Anxiety Level. The results of the statistical test using the Spearman's Rank test obtained a p-value of 0.00 (p <0.05) with an r value = 0.415 and a positive correlation direction. P value 0.00 (p <0.05) means that the research hypothesis is accepted. Conclusion: There is an influence between hospitalization on children's anxiety levels and hospitalization on children's anxiety levels. Thus, the better the hospitalization, the lower the child's anxiety level.